Feasibility of balloon endoscope-assisted endoscopic retrograde cholangiopancreatography for the elderly - Hakuta, Ryunosuke; Kogure, Hirofumi; Nakai, Yousuke; Hamada, Tsuyoshi; Sato, Tatsuya; Suzuki, Yukari; Inokuma, Akiyuki; Kanai, Sachiko; Nakamura, Tomoka; Noguchi, Kensaku; Ishigaki, Kazunaga; Saito, Kei; Saito, Tomotaka; Takahara, Naminatsu; Mizuno, Suguru; Yamada, Atsuo; Tada, Minoru; Koike, Kazuhiko (Endoscopy International Open, 2020)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) for patients with surgically altered anatomy is challenging. Recently, balloon endoscopy has been shown to facilitate ERCP for this population with a high technical success rate, but adverse events (AEs) are not uncommon. Compared to non-elderly patients, elderly patients may be at higher risk of AEs due to underlying comorbidities. The current study aimed to evaluate the feasibility of balloon endoscope-assisted ERCP (BE-ERCP) for the elderly.Patients and methods We retrospectively identified patients who underwent BE-ERCP between January 2010 and September 2019. For patients who underwent multiple procedures during the study period, the first session was analyzed. Early AEs associated with BE-ERCP were compared between elderly (≥ 75 years) and non-elderly patients.Results A total of 1,363 BE-ERCP procedures were performed, and 568 patients (211 elderly and 357 non-elderly) were included for the analyses. Technical success rates were high in both the elderly and non-elderly groups (80 % vs. 80 %, respectively). The rates of early AEs were similar between the groups (12 % vs. 9.0 % in the elderly and non-elderly group, respectively; P = 0.31). The mltivariable-adjusted odds ratio for early AEs comparing elderly to non-elderly patients was 1.36 (95 % confidence interval, 0.74–2.51; P = 0.32). Specifically, we did not observe between-group differences in rates of gastrointestinal perforation (2.4 % vs. 2.8 % in elderly and non-elderly groups, respectively; P = 0.99) and aspiration pneumonia (1.9 % vs. 0.6 %, P = 0.20).Conclusions BE-ERCP is a feasible procedure for elderly individuals with surgically altered anatomy.